Synopsis and annotated checklist of Recent marine Bryozoa from Brazil - Vieira, Leandro M.; Migotto, Alvaro E.; Winston, Judith E. (Zootaxa, 2008)
We present here a checklist of recent marine bryozoans recorded in the literature from Brazil. The total number of species recorded is 346. The most diverse group is the order Cheilostomata with 271 species, followed by the order Ctenostomata, with 42 species, and the order Cyclostomata, with 33 species. Included in the checklist are records by state and citations for species with synonyms utilized in Brazilian works.